Lenaai ole Mowuo's Zoom transcript, Kenya, June 27, 2022 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
Addresses the role of covid in Maasai groups such as Loita, Purko, Kisongo, Loodokilani. To have access to the research data file, please contact: Angela Kronenburg: angela.kronenburg@uclouvain.be
Keywords: Arid regions; Maasai (African people); Households; Vaccination; East Africa; Lockdown; Tanzania; Kenya; Border; COVID-19 Pandemic